El nitrógeno en los sistemas ganaderos de leche - Elizondo-Salazar, Jorge Alberto (Universidad de Costa Rica, 2004)
Nitrogen in dairy farm systems. Nitrogen is a very important element for all living organisms. It is present in the atmosphere, soil and water. It is applied all over the world to produce food. Nitrogen for agriculture can be supplied by inorganic fertilizer, bacterial fixation, animal manure, crop residues, and mineralization. Currently, nitrogen fertilizer is the major source of nitrogen for agriculture while N from animal manure is used inefficiently. Moreover nitrogen is being applied at higher rates than the ecosystem can handle, causing odor nuisance and water pollution, which has led to animal and human intoxication. It has also impacted water and terrestrial ecosystems. The objective of this study is to provide a brief commentary on the importance of N in the organism, understand that excess N can be an important threat to the environment and acknowledge viable and economical ways to reduce N excretion in dairy farm systems.